Microsoft SharePoint 2007 technologies planning, design and implementation - Laahs, Kevin. (Digital, 2008)
Microsoft SharePoint 2007 Technologies: Planning, Design and Implementation provides an in-depth examination of the tasks involved in planning, designing and deploying SharePoint in your enterprise. SharePoint 2007 significantly extends the breadth of capabilities for end users, administrators, developers, and designers. The cutting-edge technology encompasses some major new functional areas such as Business Intelligence, Information LifeCycle Management, and Enterprise Content Managementall can be leveraged to satisfy many different business scenarios. SharePoint 2007 Technologies will provide readers with practical knowledge and techniques about integration of other 2007 products such as Office and Exchange Server, and readers will walk away with the ability to easily expose and leverage back-end business data and understand how it all joins together. Readers will further gain a solid appreciation of the architecture, administration, end user features, development, and integration opportunities offered by SharePoint 2007. The expertise of the author team in helping many large corporations deploy Microsoft technologies within their enterprises makes this book an invaluable tool to businesses of any size. * Complete guide to getting the most out of your SharePoint 2007 deployments * Critical techniques for system architects to design and deploy SharePoint 2007 Technologies * Features most important issues for day to day efficient management and usage * How to customize and extend your SharePoint environment for your own needs.